# (2n+1)(2n-1)(n+5)

I'm a little confused on how to do this one.

Any help would be greatly appreciated!!!

Thanks.

Thank you!!!

What are you trying to do? Multiply?

The first terms will make a difference of squares (a-b)(a+b)=a^2 - b^2

(4n^2-1)(n+5) Now multiply out these two terms.

What are you trying to do? Multiply?

The first terms will make a difference of squares (a-b)(a+b)=a^2 - b^2

(4n^2-1)(n+5) Now multiply out these two terms.

## To simplify the expression (2n+1)(2n-1)(n+5), you can use the distributive property to multiply each pair of terms within the parentheses.

First, let's multiply the first two terms (2n+1) and (2n-1) using the difference of squares formula, which states that (a+b)(a-b) = a^2 - b^2. In this case, a = 2n and b = 1.

(2n+1)(2n-1) = (2n)^2 - 1^2

= 4n^2 - 1

Now we have (4n^2 - 1)(n+5). To multiply these two terms, you can use the distributive property. Multiply each term in the first parentheses (4n^2 - 1) by each term in the second parentheses (n+5).

4n^2 * n + 4n^2 * 5 - 1 * n - 1 * 5

= 4n^3 + 20n^2 - n - 5

So, the simplified form of (2n+1)(2n-1)(n+5) is 4n^3 + 20n^2 - n - 5.